SGK1 inhibition in glia ameliorates pathologies and symptoms in Parkinson disease animal models - Oh‐Chan Kwon; Jae‐Jin Song; Yunseon Yang; Seong‐Hoon Kim; Ji Young Kim; Min‐Jong Seok; Inhwa Hwang; Je‐Wook Yu; Jenisha Karmacharya; Han‐Joo Maeng; Jiyoung Kim; Eek‐hoon Jho; et al. (EMBO Molecular Medicine)
Abstract Astrocytes and microglia are brain‐resident glia that can establish harmful inflammatory environments in disease contexts and thereby contribute to the progression of neuronal loss in neurodegenerative disorders. Correcting the diseased properties of glia is therefore an appealing strategy for treating brain diseases. Previous studies have shown that serum/ glucocorticoid related kinase 1 (SGK1) is upregulated in the brains of patients with various neurodegenerative disorders, suggesting its involvement in the pathogenesis of those diseases. In this study, we show that inhibiting glial SGK1 corrects the pro‐inflammatory properties of glia by suppressing the intracellular NFκB‐, NLRP3‐inflammasome‐, and CGAS‐STING‐mediated inflammatory pathways. Furthermore, SGK1 inhibition potentiated glial activity to scavenge glutamate toxicity and prevented glial cell senescence and mitochondrial damage, which have recently been reported as critical pathologic features of and therapeutic targets in Parkinson disease (PD) and Alzheimer disease (AD). Along with those anti‐inflammatory/neurotrophic functions, silencing and pharmacological inhibition of SGK1 protected midbrain dopamine neurons from degeneration and cured pathologic synuclein alpha (SNCA) aggregation and PD‐associated behavioral deficits in multiple in vitro and in vivo PD models. Collectively, these findings suggest that SGK1 inhibition could be a useful strategy for treating PD and other neurodegenerative disorders that share the common pathology of glia‐mediated neuroinflammation.